Eukaryotic translesion synthesis: choosing the right tool for the job - Powers, Kyle T. (DNA Repair (Amst), 2018)
Normal DNA replication is blocked by DNA damage in the template strand. Translesion synthesis is a major pathway for overcoming these replication blocks. In this process, multiple non-classical DNA polymerases are thought to form a complex at the stalled replication fork that we refer to as the mutasome. This hypothetical multi-protein complex is structurally organized by the replication accessory factor PCNA and the non-classical polymerase Rev1. One of the non-classical polymerases within this complex then catalyzes replication through the damage. Each nonclassical polymerase has one or more cognate lesions, which the enzyme bypasses with high accuracy and efficiency. Thus, the accuracy and efficiency of translesion synthesis depends on which non-classical polymerase is chosen to bypass the damage. In this review article, we discuss how the most appropriate polymerase is chosen. In so doing, we examine the structural motifs that mediate the protein interactions in the mutasome; the multiple architectures that the mutasome can adopt, such as PCNA tool belts and Rev1 bridges; the intrinsically disordered regions that tether the polymerases to PCNA and to one another; and the kinetic selection model in which the most appropriate polymerase is chosen via a competition among the multiple polymerases within the mutasome.